The Symmetry of Rare-Earth Metals. The Paradox of Ce and Its Alloys. Quantum Theory. I. Ce - Mitsek, O.I.; Pushkar, V.M. (Металлофизика и новейшие технологии, 2015)
The symmetry of rare-earth metals (REM) and f.c.c.-Ce ‘paradox’ are calculated by means of the method of many-electron operator spinors (MEOS). Методом багатоелектронних операторних спінорів (БЕОС) розраховується симетрія рідкісноземельних металів (РЗМ) разом із «парадоксом» ГЦК-Ce. Методом многоэлектронных операторных спиноров (МЭОС) рассчитывается симметрия редкоземельных металлов (РЗМ), включая «парадокс» ГЦК-Ce.